2014
DOI: 10.1021/nl403717d
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Observation of Multiconformational Binding and Energy Level Alignment of Ruthenium-Based Photosensitizers on TiO2Anatase

Abstract: Dye-sensitized solar cells constitute a promising approach to sustainable and low-cost solar energy conversion. Their overall efficiency crucially depends on the effective coupling of the photosensitizers to the photoelectrode and the details of the dye's energy levels at the interface. Despite great efforts, the specific binding of prototypical ruthenium-based dyes to TiO2, their potential supramolecular interaction, and the interrelation between adsorption geometry and electron injection efficiency lack expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 50 publications
4
79
0
Order By: Relevance
“…Kley et al 29 have reported that the N3 dye molecules [cis-bis(isothiocyanato)bis(2,2 -bipyridyl-4,4 -dicarboxylato)ruthenium(II)] have two NCS groups adsorbed in numerous different states, and the state accordingly determines which S atom in the NCS interacts with the TiO 2 anatase (101). 29 We therefore assume that the S atom in NCS is not involved in strong interactions when N719 is coadsorbed with D131, but that the binding of the S atoms in N719 to the TiO 2 is strong in the single-component system. The coadsorbed D131 molecule appears to inhibit the S-mediated interaction between N719 and TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Kley et al 29 have reported that the N3 dye molecules [cis-bis(isothiocyanato)bis(2,2 -bipyridyl-4,4 -dicarboxylato)ruthenium(II)] have two NCS groups adsorbed in numerous different states, and the state accordingly determines which S atom in the NCS interacts with the TiO 2 anatase (101). 29 We therefore assume that the S atom in NCS is not involved in strong interactions when N719 is coadsorbed with D131, but that the binding of the S atoms in N719 to the TiO 2 is strong in the single-component system. The coadsorbed D131 molecule appears to inhibit the S-mediated interaction between N719 and TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, high-performance, low-temperature SPM measurements that involve tunneling spectroscopy can last several days, during which the operation of a pumping-intense, noisy ES-IBD source is impossible. Therefore, vacuum suitcases allow the transfer of samples between spatially separated, independent SPM and ES-IBD setups while maintaining UHV conditions during the entire transfer (35,36).…”
Section: Experimental Setup and Workflowmentioning
confidence: 99%
“…Similar multi-conformational adsorption geometries have recently been observed via low temperature STM of N3 on TiO 2 . 25 It is also possible that bonds to the surface can form without deprotonation, thus forming monodentate structures. 30 Aluminum oxide prepared in UHV is prone to hydroxylation even under UHV conditions, so mismatch in O 1s peak ratios could be due to presence of OH groups on the alumina surface.…”
Section: A Adsorption Bondingmentioning
confidence: 99%